Agri‐food technology politics: Exploring policy narratives in the European Parliament. (6th June 2021) - Vogeler, Colette S.; Schwindenhammer, Sandra; Gonglach, Denise; Bandelow, Nils C.
Abstract: The Narrative Policy Framework (NPF) highlights the role of arguments and emotions included in stories to influence the policy process. Most applications refer to highly politicized issues. How are narratives used in less politicized debates? This paper applies the NPF to two debates within the European Parliament (EP) which generally gain less public media attention than national debates. By conducting a discourse network analysis of two policy debates on agri‐food technologies in the EP, we show that both debates do not rely as much on emotions as compared to public debates, but are to a greater degree based on argumentative and scientifically grounded reasoning. The use of the NPF characters of victims, villains, and heroes are fairly limited. Instead, the recently introduced character of the beneficiary is used frequently to highlight the advantages and benefits of the preferred policies. 摘要: 叙事政策框架（NPF）强调叙事中用于影响政策过程的论点和情感的作用。大多数NPF的应用有关于高度政治化的议题。叙事在不太政治化的辩论中是如何使用的？本文将NPF应用于欧洲议会（EP）的两场辩论，这两场辩论整体上获得的公共媒体关注度少于国家辩论。通过对欧洲议会中两场关于农产品技术的政策辩论进行话语网络分析，我们表明，这两场辩论与公共辩论相比，前者依赖的情感因素较少，但在更大程度上基于辩论性的、科学的推理。对受害者、反面人物（villains）、正面人物(heroes)等NPF角色的使用相当少。相反，频繁使用了近年来NPF新增的受益者角色，以强调所偏好政策的优点和益处。 Resumen: El Narrative Policy Framework (NPF) destaca el papel de los argumentos y emociones incluidos en las historias para influir en el proceso de políticas. La mayoría de las aplicaciones se refieren a cuestiones muy politizadas. ¿Cómo se utilizan las narrativas en debates menos politizados? Este documento aplica el NPF a dos debates dentro del Parlamento Europeo (PE) que generalmente obtienen menos atención de los medios públicos que los debates nacionales. Al realizar un análisis de la red de discursos de dos debates políticos sobre tecnologías agroalimentarias en el PE, mostramos que ambos debates no se basan tanto en las emociones como en los debates públicos, sino que se basan en mayor medida en un razonamiento argumentativo y científicamente fundamentado. El uso de los personajes NPF de víctimas, villanos y héroes es bastante limitado. En cambio, el carácter recientemente introducido del beneficiario se utiliza con frecuencia para resaltar las ventajas y beneficios de las políticas preferidas.